Bez sensu as an act of communication - Wiesław Czechowski (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2020)
The article presents a communication-based analysis of the function of the ‘bez sensu’ [meaningless/ pointless/makes no sense etc.] phraseme. The author discusses the conversational and discursive opportunities for using it. He applies the methodology of communicational grammar, which enables the analysis of communications at the ideational and interactive levels. Within the semantic level, ‘bez sensu’ removes the value of the trivialised semantic standard. In conversations, it is the reaction to scripts which contradict natural logic and the common-sensical cause-and-effect course of things. An important function is the bringing forward of scripts of failure, wastefulness, redundancy, and lack of benefit or expected or actual harm. At the interactive level, the ‘bez sensu’ expression fulfils the function of support for the argumentative power of a communication; it is also a measure of undermining an argumentation – it emphasises the frailty of its premises. In axiological strategies, ‘bez sensu’ is a major component of emotive acts and the building block of the emotional tension between interlocutors. In this instance, it is mostly used to bring forward the experience of a negative emotion. One negative outcome of using the ‘bez sensu’ expression is the introduction distance to interpersonal contact, and in some cases the sense of intellectually debasing the sender of a communication. The article includes several examples of media-based political statements with the ‘bez sensu’ expression, which are used for discrediting political opponents.